Comprehensive analysis of microRNA and metabolic profiles in bovine seminal plasma of different semen quality - Cao, Wei; Sun, Wenqiang; Chen, Shiyi; Jia, Xianbo; Wang, Jie; Lai, Songjia (Frontiers in Veterinary Science, 2023)
Seminal plasma plays a pivotal role in modulating sperm viability and function. However, the underlying mechanisms have not been fully elucidated. In this study, the bull semen production records of core breeding farms and bull stations in the past 10 years was analyzed, and found that the semen of 5-year-old bulls collected for the first time is of the best quality (p<0.05). Despite the bull semen collected under above conditions, the low-quality sperm is still obtained from part of bulls due to individual difference. Interestingly, seminal plasma from normal semen is capable of improving low-quality semen motility. To identify the potential key factors in seminal plasma, the differences of miRNA and metabolite profiles between normal and low-quality seminal plasma were analyzed. We found that 59 miRNAs, including 38 up-regulated and 21 down-regulated miRNAs, were differently expressed. 391 and 327 significantly different metabolites were identified from the positive and negative ion models, respectively. These multiple miRNAs and metabolites collectively contribute to the motility of sperm, subsequently, affects semen quality. Together, these results not only revealed the key factors of seminal plasma improving sperm quality, but also provided potential miRNA- or metabolite-based biomarkers to identify the high semen quality.